The Role of Teachers' Beliefs in Family Engagement (Revista Innova Educación, 2021)
The school as an institution continues to be an organization made up of individuals, who can effectively alter reality within the school structure. This work consists of an exploration of the role of teachers' beliefs in family participation. For this, teaching beliefs, academic performance, expectations, and family participation were defined as fundamental concepts when it came to understanding the explored role. The objective of this work, to evaluate how teachers' beliefs affect parental participation, was approached from a review of the main investigations that have been generated in regard to the field of educational knowledge. As the central axis, beliefs are effectively deepened and among the main conclusions it is highlighted that the promotion of parental participation by teachers depends directly on the imaginary, culture, and beliefs that this group has on the positive impact or rejection of parental participation.
Keywords: Teacher beliefs; participation; parents; expectations; academic achievement